2012
DOI: 10.1002/anie.201205449
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ion‐Pairing Catalysis

Abstract: Charged intermediates and reagents are ubiquitous in organic transformations. The interaction of these ionic species with chiral neutral, anionic, or cationic small molecules has emerged as a powerful strategy for catalytic, enantioselective synthesis. This review describes developments in the burgeoning field of asymmetric ion-pairing catalysis with an emphasis on the insights that have been gleaned into the structural and mechanistic features that contribute to high asymmetric induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
453
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 938 publications
(461 citation statements)
references
References 231 publications
5
453
0
3
Order By: Relevance
“…Kobayashi et al have reported the first anionic phase-transfer reaction using tetrakis(3,5-bis(trifluoromethyl) phenyl) borate (TFPB) anion. [4][5][6] Recently, asymmetric anionic phase-transfer reactions 7,8) have been reported using chiral phosphates with an aziridinium cation 9) and N-haloammonium cations. [10][11][12][13][14][15][16][17][18] …”
mentioning
confidence: 99%
“…Kobayashi et al have reported the first anionic phase-transfer reaction using tetrakis(3,5-bis(trifluoromethyl) phenyl) borate (TFPB) anion. [4][5][6] Recently, asymmetric anionic phase-transfer reactions 7,8) have been reported using chiral phosphates with an aziridinium cation 9) and N-haloammonium cations. [10][11][12][13][14][15][16][17][18] …”
mentioning
confidence: 99%
“…1) rather than through formation of covalent adducts or lowest unoccupied molecular orbital-lowering protonation (or hydrogen bonding), which has generally required substrates containing carbonyl or imine moieties (11)(12)(13). This generalization applies to chiral phosphoric acids, which have been predominantly used in activation of the electrophile, although hydrogen bonding to the nucleophile has also been implicated as a key component (14).…”
mentioning
confidence: 99%
“…This generalization applies to chiral phosphoric acids, which have been predominantly used in activation of the electrophile, although hydrogen bonding to the nucleophile has also been implicated as a key component (14). More recently the anionic conjugate bases of chiral phosphoric acids (i.e., chiral phosphate anions) have received attention as counterions for positively charged electrophilic intermediates, wherein ion pairing with the phosphate anion provides a suitable chiral environment for subsequent enantioselective transformations of the electrophilic species (11)(12)(13). The generality of the concept of ion pair catalysis has allowed the application of these highly tunable scaffolds to a diverse range of transformations in which carbonyl or imine activation is clearly inapplicable (15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial S N 2 addition of an appropriate solvent, such as etheric solvent, and/or additive 15) to α-donor 1 would form a β-linked intermediate A, to which the following S N 2 attacked by an employed amide would afford the desired α-linked product. As in our previous report, 8) we have chosen an XB-donor/thiourea co-catalytic system for the activation of the leaving group (LG) of 1, mainly due to the following reasons: 1) XB interaction would be effective in relatively polar etheric solvent, and 2) tuning of both HB donor and XB donor would improve their ability to trap the LG via anion binding, 16) preventing the undesired rearrangement of the LG.…”
mentioning
confidence: 99%